2007
DOI: 10.1136/tc.2006.019638
|View full text |Cite
|
Sign up to set email alerts
|

“I always thought they were all pure tobacco”: American smokers’ perceptions of “natural” cigarettes and tobacco industry advertising strategies

Abstract: Although our findings support the idea advanced by some tobacco control advocates that informing smokers of conventional cigarettes' chemical ingredients could promote cessation, they also suggest that such a measure could increase the ubiquity and popularity of "natural" cigarettes. A more effective approach may be to "denaturalise" smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…We found that some people attribute a health benefit to cigarettes labelled as ‘natural’, ‘organic’, or ‘additive-free’, a finding also noted in previous studies 11–15. Additionally, the scepticism and confusion we encountered about cigarettes with these descriptors were similar to findings from documents of tobacco industry FGs 15. This study adds numerous possible reasons disclaimers do not fully negate the impact of cigarette descriptors.…”
Section: Discussionsupporting
confidence: 76%
“…We found that some people attribute a health benefit to cigarettes labelled as ‘natural’, ‘organic’, or ‘additive-free’, a finding also noted in previous studies 11–15. Additionally, the scepticism and confusion we encountered about cigarettes with these descriptors were similar to findings from documents of tobacco industry FGs 15. This study adds numerous possible reasons disclaimers do not fully negate the impact of cigarette descriptors.…”
Section: Discussionsupporting
confidence: 76%
“…The tobacco industry has invested heavily in promoting ‘additive-free’ cigarettes 29. We speculate that exposure to this advertising may have contributed to the finding that people believe added chemicals, not chemicals inherent to the tobacco leaf and burning of cigarettes, are responsible for cigarettes' toxicity.…”
Section: Discussionmentioning
confidence: 95%
“…PMI is using the same playbook in marketing IQOS around the world by promoting IQOS as sophisticated and aspirational, 7 emphasising the themes of cleanliness, customisation and sociability 6 . Based on what we have learnt from marketing of light cigarettes and natural tobacco, 42 44 as well as the results of PMI’s own research, it is likely that these claims will also be understood by consumers as reduced risk claims 34 …”
Section: Discussionmentioning
confidence: 99%